Risk management of savings accounts - Hana Džmuráňová; Petr Teplý (Charles University in Prague, Institute of Economic Studies (IES), 2014)
This paper deals with the risk management of savings accounts. Savings accounts are non-maturing accounts bearing a relatively attractive rate of return and two embedded options: a customer's option to withdraw money at any time and a bank's option to set the deposit as it wishes. The risk management of saving accounts remains a big challenge for banks and simultaneously raises serious concerns by some regulators. In this paper, we focus on the interest rate risk management of savings accounts. By constructing the replicating portfolio and simulating six scenarios for the market rate and client rates, we show that under the severest scenario, some banks in the Czech Republic might face a capital shortage up to 22% in next two years if market rates start to increase dramatically. We conclude that savings accounts are risky instruments that cannot be hedged by standard risk mitigation techniques. Since savings accounts in the Czech Republic are not subject to any special regulation yet, we propose imposing stricter regulation and supervision (the Belgium framework might be an inspiring model to consider).
Keywords: C15; G21; G11; 330; demand deposits; interest rate risk; replicating portfolio; risk management; savings accounts; simulations